Desakralisasi Doktrin ASWAJA Dalam Fenomena Da’wah NU di Masyarakat - Muhammad Athaillah (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2023)
The desacralization of the Aswaja doctrine (Ahlussunnah Wal Jama'ah) among Nahdlatul Ulama (NU) is a phenomenon that occurs in the context of the development and transformation of religious thought in Indonesia. NU, as one of the largest Islamic organizations in Indonesia, has a strong religious tradition based on Islamic teachings that follow the Ahlussunnah Wal Jama'ah tradition. In recent years, there has been a shift in the way of thinking and interpretation of religious teachings within NU circles, especially among NU kiai or ulama. The desacralization of the Aswaja doctrine refers to the separation between religious aspects and cultural or traditional aspects related to religious practices. This is reflected in a more inclusive da'wah approach, in which the understanding of the Aswaja doctrine is no longer considered the only correct path, but is understood as one of the valid interpretations within a variety of Islamic thought. This change can also be seen in the educational approach at NU's pesantren, where there is an emphasis on teaching that is more contextual, critical, and a broader understanding of Islam, as well as an understanding that respects differences and dialogue between religions. In conclusion, the desacralization of the Aswaja doctrine among NU is a phenomenon indicating a change in religious thinking and interpretation among kiai and ulama.